Comparison of External Ureteral Catheter and Double-J stent as Drainage Methods for Tubeless Percutaneous Nephrolithotomy: A Systematic Review and Meta-Analysis - Clarissa Tania; Edwin Tobing; Christiano Tansol (International Brazilian Journal of Urology)
ABSTRACT Purpose: The external ureteral catheter (EUC) and double-J stent (DJ-stent) are frequently used for drainage in tubeless percutaneous nephrolithotomy (PCNL). This study aims to compare the outcomes and effectiveness of these two methods. Materials and Methods: We conducted a detailed literature search using relevant key words on Google Scholar, Europe PMC, Medline, and Scopus databases. Continuous variables were combined using mean difference (MD), while binary variables were analysed using risk ratio (RR) with 95% confidence intervals through random-effects models. Results: Our analysis included nine studies. The results showed that EUC was associated with a significantly lower incidence of stent-related symptoms [RR 0.32 (95% CI 0.19 - 0.54), p < 0.0001, I² = 24%] compared to the DJ-stent. There were no significant differences between EUC and DJ-stent in terms of postoperative fever (p = 0.92), urine leakage (p = 0.21), perinephric collection (p = 0.85), haemoglobin drop (p = 0.06), transfusion rate (p = 0.27), VAS score (p = 0.67), analgesic requirements (p = 0.59), stone-free rate (p = 0.14), duration of surgery (p = 0.10), and duration of hospitalization (p = 0.50). Conclusion: The EUC demonstrated fewer stent-related symptoms than the DJ-stent in tubeless PCNL, while both methods showed comparable safety and efficacy. The choice between EUC and DJ-stent should consider patient preferences and surgeon expertise. Further randomized controlled trials (RCTs) with larger sample sizes are needed to affirm these results.